Pelacur imigran Cina di Pulau Pinang - Tan, Geck Choon (Pulau Pinang : Penerbit Universiti Sains Malaysia, 2013)
History of Chinese immigrant and prostitutes in years back at Pulau Pinang.
Bibliografi : mukasurat 129-137.
Keywords: Prostitutes -- Malaysia; Prostitution -- Malaysia